2007
DOI: 10.1162/pres.16.4.337
|View full text |Cite
|
Sign up to set email alerts
|

The Uncanny Valley: Effect of Realism on the Impression of Artificial Human Faces

Abstract: Roboticists believe that people will have an unpleasant impression of a humanoid robot that has an almost, but not perfectly, realistic human appearance. This is called the uncanny valley, and is not limited to robots, but is also applicable to any type of human-like object, such as dolls, masks, facial caricatures, avatars in virtual reality, and characters in computer graphics movies. The present study investigated the uncanny valley by measuring observers' impressions of facial images whose degree of realis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
317
5
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(348 citation statements)
references
References 32 publications
11
317
5
4
Order By: Relevance
“…2B), monkeys exhibited one pattern consistently: They preferred to look at unrealistic synthetic faces and real faces more than to realistic synthetic faces. The visual behavior of monkeys falls into the uncanny valley just the same as human visual behavior (2,3). Thus, these data demonstrate that the uncanny valley effect is not unique to humans, and that evolutionary hypotheses regarding its origins are tenable.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…2B), monkeys exhibited one pattern consistently: They preferred to look at unrealistic synthetic faces and real faces more than to realistic synthetic faces. The visual behavior of monkeys falls into the uncanny valley just the same as human visual behavior (2,3). Thus, these data demonstrate that the uncanny valley effect is not unique to humans, and that evolutionary hypotheses regarding its origins are tenable.…”
Section: Resultsmentioning
confidence: 63%
“…Although monkeys looked longer at dynamic versus static faces, the differences between the uncanny valley effects between the two conditions were marginal at best. Data from human subjects suggest that various static features can reliably elicit or ameliorate the uncanny valley effect (2,3,7). These features include skin texture, the distance between facial features, and the size of various facial features.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seyama and Nagayama (2007) investigated perception of static facial images and found that while this uncanny valley appears to exist, it is triggered by abnormal features. Wallraven and colleagues (1997) report that animation using motion capture data may compensate for reduced fidelity in form when participants rate variables such as sincerity and intensity of computer generated avatars.…”
Section: Discussionmentioning
confidence: 99%
“…This unsettling experience is likely due to a mismatch between appearance and behavior. At higher degrees visual fidelity in human faces, unpleasant experiences emerge, in particular related to atypical (abnormal) features [32]. Furthermore, it appears that visual fidelity does not affect the social influence an artificial entity has [44].…”
Section: Visual Fidelitymentioning
confidence: 96%